Multi‐port medium‐frequency PET topology for integrating photovoltaic generation with battery storage - Xuejiao Li; Mingyan Wang; Bingda Zhu; Chuang Liu (IET Renewable Power Generation)
Abstract This paper proposes a multi‐port medium‐frequency power electronic transformer (PET) topology for integrating photovoltaic (PV) generation with battery storage (BS). Firstly, this proposed PET provides multiple ports for renewable energy grid generation, so that it can achieve multi‐energy source management and energy complementary. Secondly, different from the conventional topology for renewable energy grid connected system, the proposed PET topology is safer and more reliable due to the separate connection of PV and BS through the voltage source converter to the primary winding of the PET. Finally, the PET only uses a single medium‐frequency transformer for voltage regulation and electrical isolation, so that it can avoid the use of DC capacitors in the traditional line/high‐frequency transformers, reduce the PET volume and its costs, as well as simplify the control strategy. The PET topology is introduced in detail and the simulation results verify the feasibility of the proposed topology.